Gas exchange and JIP-test parameters of two Mediterranean maquis species are affected by sea spray and ozone interaction - Mereu, Simone; Gerosa, Giacomo; Marzuoli, Riccardo; Fusaro, Lina; Salvatori, Elisabetta; Finco, Angelo; Spano, Donatella; Manes, Fausto (Environmental and Experimental Botany, 2011)
Mediterranean maquis coastal ecosystems are subject to multiple oxidative stresses of both natural and anthropic origin, as sea spray, drought, high irradiance and ozone. In this article it is hypothesized that the interaction of ozone and sea spray is additive as a consequence of a higher reactive oxigen species accumulation. To test the hypothesis, an experiment was conducted in an Open Top Chambers facility where plants of Quercus ilex L. and Arbutus unedo L. were exposed to two levels of ozone and two levels of sea spray. The response of the species was evaluated by measurements of structural parameters (shoot growth and leaf biomass) and physiological parameters (leaf level gas exchange and chlorophyll a ﬂuorescence). The results contradict the hypothesis as the interaction of the two stresses is antagonistic on both species. The structure of both species was negatively affected by sea spray, however the two stresses combined allowed a higher growth and leaf area in A. unedo. The leaf level physiology of A. unedo was only moderately affected by the two stresses alone and in combined, while that of Q. ilex was altered to a further extent by sea spray and by its combination with ozone: photosynthesis and efﬁciency of the PSII was reduced by sea spray while the ratio of PSII to PSI was increased; the two stresses combined, instead, decreased the PSII to PSI ratio allowing for a higher photosynthesis. It is concluded that A. unedo is more resistant than Q. ilex to the two stresses alone and in combination, that ozone and sea spray interact antagonistically, and that the activity of PSI has a key role in the stress response
Keywords: Antagonistic interaction; dark respiration; JIP-test; OTC; Oxidative stress; PSI